The geology of the southwestern part of the Uitloop Farm, northern limb of the Bushveld Complex, Limpopo, South Africa - Mapiloko, Mabatho (My University, 2020)
The research area is based on the southwestern portion of the Uitloop farm, which is located in the northern limb about 9 km northeast of Mokopane in the Limpopo province. The study involves the stratigraphic, petrological and geochemical investigation of the magmatic and metasedimentary rocks within two boreholes: Z19 and Z20, from the Uitloop farm. The main aim of this study was to utilise whole rock geochemical and mineral chemical characteristics to substantiate stratigraphic correlation with known units (the Lower Zone or the Platreef) of the northern limb, with the long-term goal to establish the Ni-Cu-PGE potential of the study area. The outcomes of the study have demonstrated that the stratigraphy at the southwestern portion of the Uitloop farm consists of magmatic rocks dominated by feldspathic pyroxenite intercalated with feldspathic harzburgite, pyroxenite, norite, gabbro, gabbronorite, leuconorite and parapyroxenite while calcsilicate and a variety of hornfels with angular inclusions form the footwall lithologies. A few lenses of orthopyroxenite are also observed within the hornfels units in borehole Z20, they consist entirely of granular orthopyroxene and can potentially be assigned to the Marginal Zone sills. Several stratigraphical and petrological similarities exist between the studied area of the Uitloop farm and the Platreef, however, unlike the Platreef which has the Main Zone lithologies forming the hanging wall, the magmatic rocks at Uitloop farm are bound by metasedimentary rocks of the Duitschland Formation. The chromite mineralisation on the southwestern part of the Uitloop farm occurs mainly as disturbed seams and patches of densely disseminated grains and accessory disseminations as well as a thin chromitite stringer at the top of the sequence in borehole Z20 hosted by feldspathic pyroxenites and feldspathic harzburgite units, similar to the Upper Chromite Zone in the Platreef as observed by Yudovskaya and Kinnaird (2010). The sulphide mineralisation, which generally increases with increasing depth towards the footwall contact, is dominated by pyrrhotite with subordinate pentlandite, chalcopyrite and pyrite. Like the Platreef, PGE mineralisation at Uitloop farm is associated with feldspathic pyroxenites, feldspathic harzburgites as well as hybrid rocks (e.g. parapyroxenite). Two styles of PGE mineralisation are noted: 1) the reef-style horizon that is associated with irregular or disturbed chromitites at the top of the intersection in borehole Z20 and 2) contact-style mineralisation rich in sulphides with modest PGE that is confined to the lower part of borehole Z19 sequence and to the footwall. The whole-rock geochemical analysis of the magmatic rocks revealed high MgO (12.2 – 27.9 wt.%) and high Cr2O3 (up to 7.7 wt.%) in ultramafic cumulates whereas low MgO (6.21 – 22.9 wt.%) and high Na2O (up to 2 wt.%) correspond to plagioclase-richer lithologies that crystallised from differentiated iii melts. Graphite-bearing pyroxenite and parapyroxenite in the footwall sequences show an increase in Al2O3 (9.7 and 10.4 wt.%), CaO (6.1 and 18.48 wt.%) and Fe2O3 (18.5 and 14.68 wt.%) contents that also indicate magma contamination, which may have influenced the development of the predominantly bottom-loaded PGE mineralisation in borehole Z19. The majority of the mafic/ultramafic samples from the studied area of the Uitloop farm recorded Cr/MgO >100 suggesting Critical Zone affinity. The REE content and distribution patterns are also consistent with the Platreef/Critical Zone melt signature. This study thus concludes that the geology of the southwestern portion of the Uitloop farm resembles the Platreef more than the Lower Zone, the studied sequence represents an offshoot formed by multiple sills or injections of melts of the Critical/Platreef type
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geosciences, University of the Witwatersrand, 2020